Control of Protein Activity and Gene Expression by Cyclofen‐OH Uncaging. (27th February 2018) - Zhang, Weiting; Hamouri, Fatima; Feng, Zhiping; Aujard, Isabelle; Ducos, Bertrand; Ye, Shixin; Weiss, Shimon; Volovitch, Michel; Vriz, Sophie; Jullien, Ludovic; Bensimon, David
Abstract: The use of light to control the expression of genes and the activity of proteins is a rapidly expanding field. Whereas many of these approaches use fusion between a light‐activable protein and the protein of interest to control the activity of the latter, it is also possible to control the activity of a protein by uncaging a specific ligand. In that context, controlling the activation of a protein fused to the modified estrogen receptor (ERT) by uncaging its ligand cyclofen‐OH has emerged as a generic and versatile method to control the activation of proteins quantitatively, quickly, and locally in a live organism. We present that approach and its uses in a variety of physiological contexts. Abstract : Photochemical liberation of cyclofen‐OH in live zebrafish cells allows the activity of proteins fused to the ERT2 receptor to be controlled. Fluorescent proteins targeted to the nucleus can be quickly released from cytoplasmic chaperones upon photoactivation. This approach was used to perturb and study physiological networks involved in development and in cancer.